Microgreen production: an evaluation of types of growing media - Lake, Julie A., author; Davis, Jessica, advisor (Colorado State University. Libraries, 2018)
Microgreens are edible vegetable, herb, and even flower plants that are harvested between 7 to 15 days after germination, when cotyledons and/or two ‘true’ leaves have emerged. Harvest parameters often vary depending on the type of plant being produced. The seedlings are harvested by cutting the hypocotyl just above the grow media, leaving the radicle behind. The hypocotyl, cotyledons, and often emerging first two 'true leaves' are the parts of the plant that are consumed. Plants in this early stage of development have a much higher nutritional content than their mature counterparts. Microgreens can be produced using a variety of growing methods, are easily grown in small or large quantities, and can be grown in almost any location. These factors make microgreens a quick growing source of nutritious food in the U.S. and globally. Researching different possible methods that can be used to grow microgreens could benefit future food supplies. Three separate, randomized replications were completed in a greenhouse setting. Each replication contained six different types of media, the grow media performance and microgreen production results were compared. Results showed the seed starter mix and the germinating media mix had the highest harvest volumes and required the least amount of water overall. Future research can include more media options, such as rockwool, vermicompost, perlite/vermiculite mix, coconut coir fibers/dust (not in a mat form), and sugarcane filter cake.
173 - Julie Lake
What Are Microgreens? Microgreens are edible vegetable, herb and flower plants that are harvested between 7 – 15 days after germination. Only the hypocotyl (stem), cotyledons (seed leaves) and up to two 'true leaves' are eaten. Why Are Microgreens Important? High Nutrient Content: Studies have shown that microgreens have up to 40% higher nutrient concentrations than their mature counterparts. Xiao, Z., Lester, G., Luo, Y., & Wang, Q. (2012). Assessment of vitamin and carotenoid concentrations of emerging food products: Edible microgreens. Journal of Agricultural and Food Chemistry, 60 (31), 7644-51. Versatility of Growing Requirements: Can be grown in about any location, using a variety of growing methods, and in small or large quantities. Research Objective: Evaluate types of growing media used to cultivate arugula (Eruca sativa) microgreens to determine which media maximizes plant growth and minimizes water use. Methods: Three separate, randomized replications were completed in a greenhouse setting. All three replications contained six different types of 5"x 5" squares of growing media, randomly placed on a growing tray. Seven grams of microgreen arugula seeds, from Johnny's Selected Seeds, were evenly dispersed on top of each type of media. Each type of growing media in all three replications received the same amount of water (measured in ml and distributed daily), sunlight and indoor environmental conditions. The arugula microgreens were harvested sixteen days after seeds were planted. The microgreens were measured by harvesting and weighing plant material from each type of media, to determine the quantity produced for each media in all three replications. The growing media performance and microgreen production results were compared. Results: The germinating mix and the seed starter mix had the highest harvest weight totals and required the least amount of water, overall. The coconut coir mat required the most amount of water. The hydroponic grow mat produced the least amount of microgreens. One type of microgreen crop was chosen for this study. Arugula (Eruca sativa) microgreen seeds were sourced from the company, Johnny’s Selected Seeds in Maine; www.johnnyseeds.com. According to the seed package the seed germination rate expected would be 95 percent. Three separate replications were randomized. The microgreen replications were grown in a 9.14 x 18.29 meters (or 30 x 60 feet/1,800 square feet), privately owned, free-standing, standard gable roof with a gutter height of 12 feet, polycarbonate sheeting over galvanized steel structure greenhouse; located near downtown Colorado Springs, Colorado in July of 2018. The average daily temperature and humidity of the greenhouse was chosen by the greenhouse operator. The overall average daily temperature inside the greenhouse was 79.88 degrees Fahrenheit. The overall average daily humidity level was 50.25 percent. The cooling system for the greenhouse environment consisted of a re-circulating evaporative pad cooling system located on the east side of the building with two mechanical fans located at the opposite end of the greenhouse, on the west wall. The three different replications of microgreen crops were planted in three 2.5H x 25.4W x 50.8L cm, shallow, seed starting, plant germination trays with slotted holes used for growing microgreens. These three slotted trays were then set into three non-slotted trays of the same size but with a greater height of 5.08 cm, to allow for water drainage from the media. After the seeds were sown, the three replications trays were completely covered for the first three days with a clear plastic humidity dome cover to allow full sunlight on the growing media and seeds; but also helped to retain humidity in the enclosure to keep the media and seeds moist. From the fourth through eighth days the clear dome cover was replaced by a similar cover but one with holes to allow some air flow to the growing seedlings but keep media moist as not all seeds germinated at the same rate depending on the type of media they were sown on. Starting on day nine through harvest, no cover of any kind was used on any of the three replication trays. Each of the six different types of growing media for each of the three replications were sized as a 32.26 cm square, with the loose media (Jiffy seed starter and Johnny’s germination media, 340 gm of loose media in each clear container) contained in 2.5 cm high clear containers with drainage holes that were then set in the slotted growing trays with the rest of the media. They were then randomly placed with one type of media in each tray using a random number generator website. All the media were soaked with the same amount of tap water prior to seed dispersal. Arugula seeds were sown by evenly dispersing 7 grams of seed onto each 32.26 cm square type of media in all three trials, leaving the seeds directly on top of the media (without covering the seeds with additional media). The three trials were placed on the greenhouse bench closest to the evaporative pad cooling system on the east side of the greenhouse.
College of Agricultural Sciences/Department of Horticulture and Landscape Architecture/Master of Horticulture/Colorado State University.
Keywords: microgreens; microgreen production; growing media; arugula; jute mat; hemp mat; coconut coir mat; hydroponic grow mat; seed starter mix; germinating mix